Analisis Pengaruh Kandungan Logam Berat Terhadap Energi Pembakaran Batubara - Hadi Kurniawan (PTE FTK UIN Ar-Raniry, 2017)
The research has been conducted to determine the effect of heavy metals on coal, where the coal comes from three different places in Indonesia. The collection and testing of samples was conducted by PT Sucofindo Padang branch. From the sample tested, the combustion energy is 6562 Kkal / Kg, 6331 Kkal / Kg and 6375 Kkal / Kg, for coal with initials A, B and C. Heavy metal testing is done using Atomic Absorption Spectrophotometer (SSA). From the test, the biggest metal concentration is metal potassium (K) followed by other metal. From the data it can be seen that Iron (Fe), Mangan (Mn), Lead (Pb) and Potassium (K) if the concentration is large, the combustion energy is small. While the two metals of Magnesium (Mg) and Calcium (K) have no effect at all. In Aluminum (Al) and Copper (Cu) metals if the concentration is large the energy is also large.